Understanding and Optimising Vertical and Horizontal Force Production for Performance in Team Sport Athletes - Dobbs, Caleb (Auckland University of Technology, 2016)
Power profiling allows greater prognostic and diagnostic information about the underlying mechanical determinants related to sports performance. To date, vertical jumps have been predominantly used in power profiling. Horizontal jumps have greater similarity with many functional movements but have received limited attention from researchers. Similarly, limited research exists concerning methods of improving acute and chronic jump performance in the horizontal plane of movement. Therefore, the aim of this thesis was to determine kinetic and kinematic variables in vertical and horizontal power profiling, compare them to measures of functional performance and to determine the effects of short term enhancement (STE) on jump performance. The results of study one (n = 19) indicated that power profiling measures, including mean force (MF) and peak force (PF), were as reliable in horizontal jump types (ICC range: 0.79 - 0.97; CV range: 6.6% - 9.1%) as in their vertical counterparts (ICC range: 0.82 – 0.97; CV range: 2.1% - 9.2%). These measures may be used with confidence. The results of study two (n = 17) suggested that many power profiling variables in horizontal counter movement jumps (CMJ), drop jumps (DJ) and squat jumps (SJ), including MF and PF, had greater relationships to sprint speeds (R 2= 0.13 to 0.58) than MF and PF in vertical jumps (R2 = 0.01 to 0.50). This suggests that, when the prognostic value of such tests to functional movements is of concern, horizontal jumps should be used alongside their vertical counterparts. Further, it is likely that horizontal dynamic training may have greater transfer to sprint performance than vertical dynamic training. Study three explored the effects of STE on horizontal jump performance in developmental rugby players (n = 24). Four minutes post pre-intervention (4RM squats), STE caused meaningful small improvements in horizontal jump performance, including MF in CMJ (effect size (ES) = 0.51 ± 0.38) and DJ (ES = 0.45 ± 0.41). This demonstrates that STE is not specific to the plane of movement of the intervention and that subjects need not be highly trained to achieve STE. This effective STE protocol was used to determine the training effect of contrast training in study four (n = 20). A matched pairs seven-week training intervention was implemented with a contrast (STE affected) and complex (control) training group. Differences in mean change of vertical and horizontal CMJ measures of force (ES Range = 0.40 - 0.46 ± 0.37 - 0.63), vertical CMJ peak velocity (ES = 0.84 ± 0.66) and mean velocity (ES = 0.62 ± 0.88) were meaningfully greater in the experimental training group. This demonstrates that an acute STE response in dynamic training movements can produce chronic improvements to a greater extent than identical training methods that do not elicit STE. The results of these studies indicate that measures of horizontal power profiling are reliable and tend to have greater correlation to functional performance than their vertical counterparts. As such, they may be of greater prognostic and diagnostic value for team sport athletes. Furthermore, STE was found to improve both acute and chronic measures of horizontal jump performance. The use of horizontal jumps in dynamic testing and training should be considered by strength and conditioning practitioners concerned with developing lower limb dynamic ability for functional performance.
Keywords: Jump; Horizontal; Vertical; Force; Velocity; Power; Muscle architecture; Fascicle length; Fascicle angle; Power profiling; Muscle stiffness